Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Studies on the history of Quebec, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

Powers of desire the politics of sexuality - Snitow, Ann Barr; Stansell, Christine; Thompson, Sharon (New feminist library, 1983)
This provocative anthology brings together a diverse group of well-known feminist and gay writers, historians, and activists. They are concerned not only with current sexual issues-abortion, pornography, reproductive and gay rights-but they also raise a host of new issues and questions: How, and in what ways, is sexuality political? Is the struggle for sexual freedom a complement to other struggles for liberation, or will it detract from them? Has the sexual revolution diminished or enriched the lives of women?
Keywords: approches et analyses; cours; discipline; histoire; intersectionnalité; justice sociale; lesbianisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; thématiques; études féministes